A Meta-analysis of the risk factors of deep venous thrombosis in patients undergoing hip surgery - WANG Yeting; LIU Pingfang; SUN Yuying; WEI Shiyi; ZHANG Zhen (Yixue xinzhi zazhi)
Objective To identify the risk factors for deep venous thrombosis (DVT) in patients undergoing hip surgery by Meta-analysis.Methods The Cochrane Library, Web of Science, PubMed, Embase, CNKI, VIP, WanFang and SinoMed databases were searched for the risk factors of DVT in patients undergoing hip surgery. The search period was from inception of the database to March 28, 2024. According to certain inclusion and exclusion criteria, two researchers independently screened the literature, extracted data and evaluated the literature quality. RevMan5.4 software was used to conduct the Meta-analysis.Results A total of 36 articles were included, including 30 case-control studies and 6 cohort studies, with a sample size of 83,902 cases. These included 55 risk factors. The results of Meta-analysis showed that advanced age [OR=2.11, 95%CI(1.70, 2.64)], female [OR=2.35, 95%CI(1.57, 3.51)], diabetes [OR=2.03, 95%CI(1.66, 2.49)], hypertension [OR=2.67, 95%CI(1.86, 3.84)], combined lower extremity venous disease [OR=4.30, 95%CI(2.74, 6.74)], method of anesthesia [OR=2.02, 95%CI(1.38, 2.95)], long operation duration [OR=2.46, 95%CI(1.82, 3.31)], postoperative bed time>2 d [OR=3.60, 95%CI(1.95, 6.65)], combined with blood hypercoagulability [OR=3.47, 95%CI(1.67, 7.21)], infection [OR=5.04, 95%CI(3.45, 7.37)], elevated D-dimer [OR=1.88, 95%CI(1.24, 2.84)], elevated BMI[OR=2.44, 95%CI(1.88, 3.17)], elevated triglyceride level [OR=2.51, 95%CI(1.32, 4.77)] were independent risk factors for DVT in patients undergoing hip surgery.Conclusion In hip surgery, advanced age, female, diabetes mellitus, hypertension, lower limb venous disease, anesthesia mode, long operation duration, postoperative bed time>2  d, blood hypercoagulability, infection, elevated BMI, elevated D-dimer, elevated triglyceride level are risk factors affecting postoperative DVT. Therefore, it is important to take effective preventive measures and monitoring methods in time to reduce the incidence of DVT after hip surgery.